2016
DOI: 10.1371/journal.pone.0153242
|View full text |Cite
|
Sign up to set email alerts
|

The Delayed Risk Stratification System in the Risk of Differentiated Thyroid Cancer Recurrence

Abstract: ContextThere has been a marked increase in the detection of differentiated thyroid carcinoma (DTC) over the past few years, which has improved the prognosis. However, it is necessary to adjust treatment and monitoring strategies relative to the risk of an unfavourable disease course.Materials and MethodsThis retrospective study examined data from 916 patients with DTC who received treatment at a single centre between 2000 and 2013. The utility of the American Thyroid Association (ATA) and the European Thyroid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
32
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(36 citation statements)
references
References 24 publications
4
32
0
Order By: Relevance
“…However, there is no information to which risk-group the patients with cancer-related death were classified. Similar to Castagna study, Kowalska et al (2016) calculated PPV, NPV and PVE. Their results were concordant with the data reported in Castagna et al (2011), where DRS showed the highest ability in a prediction of DTC outcomes, with PPV, NPV and PEV 56.8, 98.5 and 56.7%, respectively (Kowalska et al 2016).…”
Section: :11mentioning
confidence: 70%
See 4 more Smart Citations
“…However, there is no information to which risk-group the patients with cancer-related death were classified. Similar to Castagna study, Kowalska et al (2016) calculated PPV, NPV and PVE. Their results were concordant with the data reported in Castagna et al (2011), where DRS showed the highest ability in a prediction of DTC outcomes, with PPV, NPV and PEV 56.8, 98.5 and 56.7%, respectively (Kowalska et al 2016).…”
Section: :11mentioning
confidence: 70%
“…Another paper, confirming the relevance of DRS, involved into a retrospective analysis a group of 916 DTC patients treated with total thyroidectomy and RAI ablation in a single institution between the years 2000 and 2013 24:11 (Kowalska et al 2016). Likewise, the patients underwent an initial staging according to ATA 2009 (Cooper et al 2009) and ETA 2006(Pacini et al 2006 guidelines and were restratified 9-12 months after primary treatment (DRS) on the basis of response criteria proposed in Momesso & Tuttle (2014) as having an excellent response, biochemical incomplete response, structural incomplete response or indeterminate response.…”
Section: :11mentioning
confidence: 97%
See 3 more Smart Citations